EVALUASI RISK DAN RETURN PERUSAHAAN SEKTOR PERTANIAN - Dhistianti Mei Rahmawan Tari (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
The purpose of this study is to analyze the which listed companies in Agriculture Sector at Indonesia Stock Exchange has the most optimal financial performace . The population of this study are companies listed in Agriculture Sector at Indonesia Stock Exchange during January 2017 to December 2019.. The research sample used purposive sampling. The data sourced is monthly stock price downloaded from the Indonesia Yahoo Finance website. The analytical method used is a comparative analysis model. The methods studied are Risk Adjusted Return, Sharpe Ratio, Treynor Ratio and Jensen Alpha Ratio. The findings of this study is PT. Sampoerna Agro Tbk. (SGRO) has the most optimal financial performance, followed by PT. Sinar Mas Agro Resources and Tech Tbk (SMAR) and PT. Perusahaan Prkbn Lndn Smtr Indnsa Tbk. (LSIP) during the periode of the research.